Pengaruh Komitmen dan Motivasi Terhadap Kinerja Guru Melalui Kreativitas Pada Sekolah Dasar Swasta Kabupaten Serang - Handayani, Wahyu; Affandi, Naufal; Umalihayati, Umalihayati (Universitas Negeri Padang, 2024)
The purpose of this study is to find and analyze the influence of commitment and motivation on teacher performance through creativity in private elementary schools in Serang Regency. This type of research is quantitative descriptive using surveys. The number of samples in this study was 189 private elementary school teachers in Serang Regency, using the Proportional Random Sampling method. Data is processed using Smart PLS 3.2.9, the test results reveal that the commitment variable has a positive and significant effect on teacher performance. The commitment variable does not have a positive and significant effect on creativity. The motivation variable has a positive and significant effect on teacher performance. The motivation variable has a positive and significant effect on creativity. The creativity variable does not have a positive and significant effect on teacher performance. The creativity variable does not mediate the effect of commitment on teacher performance. The creativity variable does not mediate the influence of motivation on teacher performance.